Didactic sequence on insects for elementary School Students (Research, Society and Development, 2022)
The teaching of insects aims to encourage students to learn about their biodiversity and importance in the ecosystem, but it is recurrent to find that this theme is developed in the school environment in a fragmented way. The search for different didactic strategies and new teaching methodologies effectively contributes to resolving the fragmentation of teaching and favoring student learning. Thus, the aim of the present study was to develop and apply a didactic sequence for the teaching of the theme "insects" capable of providing students with a global view of the contents by promoting theoretical and practical activities. For the development of teaching activities, were used the resources of PowerPoint and entomological box and the application of pre-test and post-test to compare the impact of the intervention in the teaching-learning process of the students. The results indicated that the didactic sequence developed favored learning about insects, promoting greater interest and motivation of students in participating in the construction of knowledge.